Identifying the critical management aspects for diabetic patients A qualitative study - Farshad Falahati; Khalil Alimohammadzadeh; Seyed Mojtaba Hosseini; Ali Maher; Mehrnoosh Jafari (Journal of Education and Health Promotion, 2025)
BACKGROUND: Health leaders globally, especially those in Iran, bear the significant responsibility of ensuring healthcare quality for individuals with diabetes. As a result, conducting comprehensive studies to gain insights into various aspects of diabetes management and developing research-based models and strategies to improve the quantity and quality of services is crucial. This study aims to create a management model for delivering services to diabetic patients within the Iranian healthcare system. MATERIALS AND METHODS: This research adopts a qualitative-quantitative approach, utilizing multiple techniques to support the study’s findings. An 18-month prolonged engagement period, from July 2021 to November 2022, was established with participants, data, and stakeholders. To ensure questionnaire validity and reliability, SPSS software was employed for Cronbach’s alpha, CVI, and CVR indices. Model validation was conducted through confirmatory factor analysis using Lisrel software version 8.8, with the chi-square test confirming the model. RESULTS: Our research indicates that effective management of diabetic patients relies on responsive leadership, characterized by vigilant monitoring and meticulous organization. The practical application of responsive leadership in diabetes management within workplace conditions involves two key resources: human resources and financial resources, along with proficient management of information and medical technology. CONCLUSION: The study’s findings highlight the crucial role of influential responsive leaders in providing essential financial support to enhance diabetes care in healthcare organizations. Moreover, initiatives are needed to motivate managers and healthcare professionals to operate efficiently. Thus, the commitment to improving the quality of patient care must be deeply embedded in the organizational culture.